Prevention of poststroke cognitive decline: ASPIS – a multicenter, randomized, observer‐blind, parallel group clinical trial to evaluate multiple lifestyle interventions – study design and baseline characteristics. Issue 4 (10th November 2013) - Brainin, Michael; Matz, Karl; Nemec, Matthias; Teuschl, Yvonne; Dachenhausen, Alexandra; Asenbaum‐Nan, Susanne; Bancher, Christian; Kepplinger, Berthold; Oberndorfer, Stefan; Pinter, Michaela; Schnider, Peter; Tuomilehto, Jaakko; et al.
<x xml:space="preserve">Abstract</x> Background Cognitive impairment after stroke is a considerable burden to patients and their caregivers and occurs in one‐third of stroke survivors. No strategy to prevent cognitive decline after stroke exists thus far. Established vascular risk factors have been associated with cognitive decline and may be a target for therapeutic interventions in stroke survivors. Aim To test whether intensive multifactorial non‐pharmacologic interventions based on lifestyle modification can reduce the risk of cognitive decline in patients who recently suffered ischemic stroke. Methods A randomized, controlled, multicenter, observer‐blind trial was designed. The reference group obtains stroke care according to standard guidelines. The intervention group additionally receives intensive control and motivation for better compliance with prescribed evidence‐based medication, regular blood pressure measurements, healthy diet, regular physical activity and cognitive training. Primary outcomes are the rate of cognitive decline at 24 months, assessed by a neuropsychological test battery and the cognitive subscale of the Alzheimer's Disease Assessment Scale. Results 202 patients (29% women), aged 62 ± 9 years, were recruited during 2010 to 2012. Stroke related impairment at inclusion was low (mean National Institutes of Health Stroke Scale: 1.9±1.8, median modified Rankin Scale: 1 (0‐1)). At baseline, groups did not differ significantly in demographic, clinical or lifestyle characteristics. Conclusion The recruitment was successful and the groups are balanced regarding potential confounding variables. The study will provide essential data about the feasibility and efficacy of lifestyle intervention after stroke in order to develop a new approach to prevent cognitive decline in patients with mild ischemic stroke.